An INTERNAL AUDIT EFFECTIVENESS AND VALUE FOR MONEY ON SUSTAINABLE PUBLIC PROCUREMENT IN SOES IN BENGKULU CITY - Apriliyani, Natasya Dwi; Puspita, Lisa Martiah Nila Puspita (IPSAR (International Public Sector Accounting Review), 2024)
This study focuses on examining the effectiveness of internal audit and its value in achieving sustainable public procurement. The research was conducted using SMART-PLS version 4 and involved 30 state-owned enterprises in Bengkulu. The participants in the study were internal audit officers and finance officers responsible for procurement. Data collection involved the distribution of questionnaires offline, with 30 companies receiving and returning 30 questionnaires. The findings from the study using SMART-PLS version 4 indicate that: (1) the effectiveness of internal audit does not have a direct impact on sustainable public procurement, (2) internal audit effectiveness has a direct impact on value for money, (3) value for money has a direct and positive impact on sustainable public procurement, and (4) value for money mediates the relationship between internal audit effectiveness and sustainable public procurement.Keywords: efektivitas internal audit, value for money and sustainable public procurement